Community engagement in the Aboriginal Families Study: Strategies to promote participation. Issue 1 (February 2019) - Weetra, Donna; Glover, Karen; Miller, Roxanne; Wilson, Rikki; Leane, Cathy; Stuart-Butler, Deanna; Mitchell, Amanda; Gartland, Deirdre; Brown, Stephanie
Abstract: Background: Aboriginal women and families are under-represented in Australian research on pregnancy and childbirth. The Aboriginal Families Study aimed to investigate the views and experiences of a representative sample of women giving birth to an Aboriginal baby in South Australia between July 2011 and June 2013, using methods designed to respect Aboriginal culture and communities. Methods: A team of 12 Aboriginal researchers facilitated community engagement and recruitment of Aboriginal and non-Aboriginal mothers of Aboriginal infants in urban, regional and remote areas of South Australia over a two-year period. Results: A total of 344 women took part, around a quarter of all Aboriginal women giving birth in South Australia in the study period (39% urban, 35% regional and 25% from remote areas). Participants were representative in relation to maternal age (mean age of 25 years, range = 15–43 years). Over half of women (56%) first heard about the study via a member of the fieldwork team making contact with them through community connections. Other major sources of recruitment were: Aboriginal health services/programs (20%) and public maternity hospitals (16%). Almost all of the women (95%) recruited via community networks of the fieldwork team completed the questionnaire. In contrast, 51% of women recruited via public hospitals completed the questionnaire (odds ratio = 0.1, 95% confidence interval 0.0–0.1, p < 0.001). Conclusions: Aboriginal researchers' community knowledge and leadership is critical to the conduct of successful Aboriginal health research. High levels of participation in research by 'harder to reach' populations are achievable when researchers take time to build relationships and work in partnership with communities.